2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5461981
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Sensing Based Positioning Using RSS of WLAN Access Points

Abstract: Abstract-The sparse nature of location finding problem makes the theory of compressive sensing desirable for indoor positioning in Wireless Local Area Networks (WLANs). In this paper, we address the received signal strength (RSS)-based localization problem in WLANs using the theory of compressive sensing (CS), which offers accurate recovery of sparse signals from a small number of measurements by solving an ℓ1-minimization problem. A pre-processing procedure of orthogonalization is used to induce incoherence n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 18 publications
0
94
0
Order By: Relevance
“…From each grid, we collected 35 RSS values through 5-s intervals, periodically. Discussions in [24,25] showed that using numerous signal values at each grid helps to make the machine easily adapt to the Wi-Fi signal fluctuations. During RSS collections, we also record BSSIDs, which help to identify the RSS values uniquely.…”
Section: Experimental Data Acquisitionmentioning
confidence: 99%
“…From each grid, we collected 35 RSS values through 5-s intervals, periodically. Discussions in [24,25] showed that using numerous signal values at each grid helps to make the machine easily adapt to the Wi-Fi signal fluctuations. During RSS collections, we also record BSSIDs, which help to identify the RSS values uniquely.…”
Section: Experimental Data Acquisitionmentioning
confidence: 99%
“…Other research activities have been carried out to design robust RSS-based localization algorithms using probabilistic models and calibration enhancements [27], [28], [29], [30]. Compressive sensing based localization has been addressed in [20], [21] for sparse target estimation via 1 -minimization program.…”
Section: A Rss-based Localizationmentioning
confidence: 99%
“…We exploit the use of compressive sensing (CS [19]) techniques to reduce complexity since they allow the recovery of sparse signals with far fewer noisy measurements than that predicted by the Shannon-Nyquist sampling theorem. Unlike several existing solutions [20], [21], we aim to provide an online CS scheme to recover sparse signals by reading and handling dynamic amounts of noisy measurements at runtime in vehicular networks. Feng et al [20] used CS to localize only one mobile target from multiple stable reference nodes, which is vastly simpler than the problem we attempt to solve, which requires looking up multiple targets from a single mobile vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Network based navigation systems use technologies such as GPS/A-GPS, Bluetooth [19], Ultra Wide Band (UWB) [17,18], Wi-Fi [20,22,23,33,34], Radio Frequency Identification (RFID) [21,24], infrared [25] or NFC [5]. Positioning accuracy varies according to the technology implemented.…”
Section: Literature Reviewmentioning
confidence: 99%